A density functional study of structural, electronic and optical properties of titanium dioxide: Characterization of rutile, anatase and brookite polymorphs. (March 2015) - Mohamad, Mazmira; Ul Haq, Bakhtiar; Ahmed, R.; Shaari, A.; Ali, N.; Hussain, R.
Abstract: Study of fundamental physical properties of titanium dioxide (TiO2 ) is crucial to determine its potential for different applications, such as study of electronic band gap energy is essential to exploit it for optoelectronics and solar cell technology. We present here investigations pertaining to structural, electronic and optical properties of rutile, anatase and brookite polymorphs of TiO2 by employing state of the art full potential (FP) linearized (L) augmented plane wave plus local orbitals (APW+lo) approach realized in WIEN2k package and framed within density functional theory (DFT). To incorporate exchange correlation(XC) energy functional/potential part into total energy, these calculations were carried out at the level of PW–LDA, PBE–GGA, WC–GGA, EV–GGA, and mBJ–GGA which are exploited as the manipulated variables in this work. From our computations, the obtained structural parameters results were found to be consistent with the available experimental results. The analysis of electronic band gap structure calculations point to TiO2 as a semiconducting material in all three phases, whereas band gap character around Fermi level was found to be indirect for anatase, and direct for rutile and brookite phases. Density of state (DOS) profiles showed a substantial degree of hybridation between O 2p and Ti 3d in conduction and valence band regions, illustrating a strong interaction between Ti and O atoms in TiO2 compund. In addition, our investigations of the optical properties also endorse the interband transitions from O 2p in valence band to Ti 3d in conduction band.